2021
DOI: 10.22271/phyto.2021.v10.i3a.14062
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants with anticancer effects available in Bangladesh: A review

Abstract: Cancer is one of the most death causing diseases and the number of cases rising around the world. So, there is a developing demand to get a durable cure to treat this awful disease. Currently, conventional techniques such as chemotherapy are not suitable for their destructive post-treatment outcomes and sometimes it is not a budget-friendly option to every person. Various medicinal plant acquired metabolites have become the core of interest due to their fewer side effects and variable application in averting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…The study findings are supported by earlier observations showing alkaloids, carotenoids, glycosides, polyphenols, polysaccharides, saponins, and terpenoids in medicinal plants as potential inhibitors of PL [31]. Likewise, Khatun et al [32] reported the presence of alkaloids, terpenoids, tannins, and cardiac glycosides in the M. micrantha 70% ethanol extracts [30]. The same was expected for alkaloids, tannins, cardiac glycosides, and terpenoids found in the ethyl acetate extracts of M. micrantha such as caryophyllene, germacrene D, and thujopsene, which are promising PL inhibitors [4].…”
Section: Pancreatic Lipase (Pl) Inhibitory Activitysupporting
confidence: 88%
“…The study findings are supported by earlier observations showing alkaloids, carotenoids, glycosides, polyphenols, polysaccharides, saponins, and terpenoids in medicinal plants as potential inhibitors of PL [31]. Likewise, Khatun et al [32] reported the presence of alkaloids, terpenoids, tannins, and cardiac glycosides in the M. micrantha 70% ethanol extracts [30]. The same was expected for alkaloids, tannins, cardiac glycosides, and terpenoids found in the ethyl acetate extracts of M. micrantha such as caryophyllene, germacrene D, and thujopsene, which are promising PL inhibitors [4].…”
Section: Pancreatic Lipase (Pl) Inhibitory Activitysupporting
confidence: 88%
“…Zahin and Ahmad (2009) [54] found DPPH scavenging activity of 77.0% in H. indicus root. Saha et al (2013) [39] reported DPPH scavenging activity of 80.03% in H. indicus root. found DPPH scavenging activity of 84.72% in H. indicus root.…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…(28). These therapies might induce stress in patients, which can lead to health problems as a result of the medicines' negative effects (29,30). As a result, alternative treatments and therapies are becoming more popular.…”
Section: Introductionmentioning
confidence: 99%